Revolutionizing Organizational Communication in Industry 4.0: Unlocking Opportunities and Overcoming Challenges in Bangladesh - Shahriar, Fahim; Tonmoy, Md. Shahriar Bulbul; Yeasmin, Farhana (UIN Sunan Gunung Djati Bandung, 2024)
This paper examines the impact of Industry 4.0 on organizational communication, exploring the opportunities and challenges presented by this revolutionary paradigm shift. The study employs a qualitative research methodology, drawing on academic literature, case studies, and in-depth interviews with national and international organizations. By evaluating the importance of effective communication in the Internet of Things (IoT) era, the paper assesses the opportunities and identifies the challenges of Industry 4.0 in organizational communication. The study delves into the complex relationship between technology and communication, outlining best practices for implementing communication tools and artificial intelligence (AI) in Industry 4.0. Effective communication is crucial for success in Industry 4.0, as it enables individuals to collaborate effectively and share ideas, leading to improved decision-making and problem-solving. However, information overload, miscommunication, and isolation risks must be mitigated to ensure effective communication. Investing in employee training and development, establishing clear communication protocols, and balancing virtual and face-to-face communication can help organizations manage these risks effectively. Mitigating the risks associated with organizational communication in Industry 4.0 is crucial to ensure that organizations can successfully leverage the opportunities presented by this era of digitalization. Recommendations include adopting cybersecurity measures, streamlining communication processes, protecting personal information, ensuring clarity and transparency, regularly updating data security measures, and promoting inclusive communication to overcome social barriers and ensure sustainable organizational communication.